ISOLATION AND CHARACTERIZATION OF ANTIFUNGAL ACTINOMYCETE FROM THIRUPORUR FORESTS - R.V.SHALINI,; DR.K.AMUTHA, (International Journal of Pharma and Bio Sciences, 2015)
Nearly sixty isolates of bacteria, fungi and actinomycetes were selected from ten soil samples. The soil samples were collected from the Thiruporur forest area. Among the sixty isolates, we selected twenty isolates of actinomycetes. These actinomycetes were isolated from soil samples by the serial dilution method. They were subjected to primary screening. After the primary screening three actinomycetes named A3, A7 and A20 were selected on the basis of zones of inhibition produced around them. This was followed by secondary screening against Aspergillus fumigatus (streak culture) which was the target pathogen. The isolate A7 showed prominent antifungal activity after the secondary screening, hence it was selected for further study. It was subjected to morphological and molecular methods to reveal its identity.